Ending the Chase for a Perfect Binder: Role of Surface Chemistry Variation and its Influence on Silicon Anodes. Issue 18 (18th September 2020) - Hays, Kevin A.; Armstrong, Beth; Veith, Gabriel M.
Abstract: In this work we examine the influence of the type of silicon source material (two milled and two plasma enhanced chemical vapor deposition) on the electrochemical performance of silicon‐based anodes for Li‐ion batteries. The four representative Si sources were previously identified in literature but have never been compared side by side, which is critical to understanding the wide variation in performance reported for silicon‐based electrodes. These particles display unique surface features associated with surface oxides and residual precursor species (Si−N, Si−C, Si−H) which impact processability by changing interactions within the electrode slurry and the resulting electrochemical performance. These properties should be taken into consideration when utilizing "off‐the‐shelf" Si powders for investigations and would be good variables to explore to understand why certain chemistries display suitable performance, while others "don't work." Abstract : A side‐by‐side comparison : We explore the surface chemistry of four commercially available silicon materials and identify that performance is related to surface potential. The optimal surface potential improves mixing through colloidal stabilization in solution resulting in intimate contact within the slurry components.